Rekonstruksi Hak Hadhanah dalam Hukum Keluarga Islam: Analisis Yuridis Pemberian Hak Asuh Anak kepada Ayah Pasca Perceraian - Adila Syaidatun Nisa; Fitria Adzuhri Mahyudin; Tufatul Kholisoh; Muhammad Hapipi Roif; Rafli Ramdan; Ahmad Fahrul Fauji (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Divorce not only ends a marriage, but also has serious implications for the fulfillment of children's rights and welfare, particularly in terms of custody (hadhanah). Children are the most vulnerable to psychological, emotional, and social impacts resulting from parental conflict after divorce. In Islamic family law, custody rights for children who have not reached the age of discernment are, in principle, given to the mother as stipulated in Articles 105 and 156 of the Compilation of Islamic Law. However, in judicial practice, these custody rights can be transferred to the father if the mother is deemed incapable of ensuring the safety, welfare, and development of the child. This study aims to analyze the provisions of child custody in Islamic family law, identify the factors behind the granting of custody to the father, and examine the legal considerations in the determination. The research method uses a qualitative approach with normative legal techniques through a literature study of Islamic legal sources, laws and regulations, and academic literature. The results of the study show that granting custody to the father is legally justified if it better ensures the welfare and best interests of the child, which is the main principle in Islamic family law after divorce.